MHD-stirring of a heavy impurity under a rotating magnetic field generated by a multi-section inductor - Okatev, Roman Sergeyevich; Losev, Gennadiy Leonidovich; Kolesnichenko, Il′ya Vladimirovich (Computational Continuum Mechanics, 2025)
We study numerically the efficiency of stirring a two-phase dispersed fluid (liquid metal with impurity particles) in a cylindrical cell using a multiphase two-fluid model. The stirring is driven by an electromagnetic force generated by a sectional rotating magnetic field inductor. The inductor consists of six annular segments evenly distributed along the height of the cell. Each segment generates a rotating magnetic field independently. We consider three electromagnetic force configurations. The first configuration corresponds to a co-directional rotation of the magnetic fields of all six inductors, matching the case of a classical rotating magnetic field. In the second configuration, the three upper rings generate a magnetic field rotating in one direction, while the lower three rotate in the opposite direction. In the third configuration, the rotation directions of the magnetic fields alternate along the cell height. We introduce a parameter characterizing the inhomogeneity of the impurity distribution. It was shown that the most efficient mixing is achieved in the second configuration, which is attributed to the emergence of a large-scale oscillatory flow regime. The uniform rotating magnetic field configuration provides the least efficient mixing due to low poloidal velocity. In the third configuration, oscillations in the impurity distribution inhomogeneity parameter associated with the chaotic nature of the flow are observed. The optimal stirring time at which the degree of impurity distribution inhomogeneity is the least is determined.